Formação de professores de Matemática, Física e Química na perspectiva da inclusão de estudantes com deficiência visual : análise de uma intervenção realizada em Rondônia - Uliana, Marcia Rosa (2015)
This present thesis inserts in the line of Teacher Training and aimed to investigate what extent a discipline/course training of future teachers of Mathematics, Physics or Chemistry, focused on teaching strategies for students with visual impairments, contributes to teacher training, in a view of to promote inclusive education. The study consisted in an action-research oriented by methodological framework of the qualitative approach and the investigative process happened in three phases. In the first phase - Exploratory / Diagnostic - the intention is to make a panoramic reading to how is happening teacher training, in view of the person's education process with visual impairment in the state of Rondônia, research locus. For this, educational projects were analyzed in five classroom presential degree courses in Mathematics, Physics and Chemistry, offered by the institutions of the state. We also heard four teachers of Mathematics, Physics and Chemistry that work in High School, three students with visual disabilities of high school and 54 undergraduates in the final stages of the mentioned courses. The second phase – Training Actions - it was planned and developed a training course attended by 26 undergraduate students in Mathematics, Physics and Chemistry. In the third phase - Evaluation - aimed to know the effect of a discipline / course on the inclusion theme of students with visual impairment in the formative process of undergraduates. The tools used to produce / collect data together the 87 participants that were involved, were: questionnaires, semi-structured interviews, diary of camp, video recordings and narratives / teaching cases. The data were analyzed by content analysis technique and the theoretical dialogue took place with authors discussing teacher training, knowledge’s, historical trajectory of people with disabilities, education of the person with disabilities, Inclusive Education and Teaching of Mathematics, Physics and Chemistry. In addition, we correlate the data obtained with the laws, documents and statements, national and international, which deal with and sustains the education of persons with disabilities. The data from the first phase of the research showed that students with visual impairments of high school enrolled in state schools in Rondônia are not living a truly inclusive process and that the student education theme with disabilities is missing or too timidly in the educational projects of the courses analyzed of undergraduate. Teachers who are teaching classes for students with disabilities did not have pedagogical training for this in their initial training, neither in continuing education processes. Graduates of undergraduate programs analyzed, too, do not feel prepared to promote an inclusive education for students with visual impairments. However, data produced / collected in intervention, revealed that the discipline / course focused on teaching strategies for students with visual impairment, has generated multiple and significant contributions, that with regard mainly the teaching knowledge to promote an inclusive education for students with visual impairment. To close the reflective spiral to the undergraduate to remake the perceptions which had about the visually impaired and they passed to realize the inclusion of students with visual impairment as something possible through differentiated pedagogical actions. Among the developed training strategies, which showed that were more productive / significant in preparation for the promotion of inclusive education they were correlated theory and practice, as production and didactic material test.